2008
DOI: 10.1055/s-0039-1697390
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Preheating on the Mechanical Properties of Resin Composites

Abstract: ObjectivesThe purpose of this study was to compare the flexural strength and modulus of two commercial resin composites, at room temperature and 40, 45 and 50°C prior to light polymerization with standard and step-cure protocols.MethodsOne nanohybrid (Grandio, VOCO, Cuxhaven, Germany), and microhybrid composite resin (Filtek Z250, 3M ESPE, St. Paul, MN, USA) were used. The materials were inserted into rectangular moulds at room temperature or preheated to a temperature of 40, 45 or 50°C and cured with standard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
52
2
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(62 citation statements)
references
References 33 publications
(44 reference statements)
0
52
2
1
Order By: Relevance
“…This could result in improved mechanical properties. Whether preheating could improve the mechanical and physical properties or not of microhybrid universal composites Z250 3MEspe and nanohybrid composite resins Grandio Voco; it is a question needed to be verified (25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could result in improved mechanical properties. Whether preheating could improve the mechanical and physical properties or not of microhybrid universal composites Z250 3MEspe and nanohybrid composite resins Grandio Voco; it is a question needed to be verified (25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
“…The high viscosity of heavily filled materials, as packable composites and microhybrid composites, may create a difficulty in producing a good marginal adaptation which may lead to void formation especially at the critical gingival margin (26). Therefore, microhybrid composite was selected for this study as it was suggested that preheating increased its flow properties, and hence improved its handling characteristics as reported by knight et al (28), in 2006.…”
Section: Discussionmentioning
confidence: 99%
“…[9] Daronch et al . found no significant differences in the intrapulpal temperature between room temperature and preheated resin composite at similar restorative stages.…”
Section: Discussionmentioning
confidence: 99%
“…One of these studies investigated the effect of pre-warming on flexural strength and found significance in some but not all tested composites [11]. In contrast Fróes-Salgado et al and Uctasli et al reported no significant difference in flexural strength between preheated and room temperature composite [14, 21]. Further investigation is warranted in this respect.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, two other studies found no significant difference in flexural strength between heated and nonheated composites [14, 21]. It is worth mentioning that those three studies evaluated different composite brands and this may explain different findings as different brands may behave differently due to differences in monomer composition and fillers type and size.…”
Section: Introductionmentioning
confidence: 93%